Systematic Review: The Effect of Covid-19 on Anxiety in Pregnant Women - Anita Dewi Anggraini; Budi Prasetyo; Rachmah Indawati (Institute of Computer Science (IOCS), 2022)
Pregnancy is a very vulnerable period in a woman's life. Hormonal changes during pregnancy can affect emotional instabilityThe anxiety caused will have an impact on the health of mothers and children such as the risk of preeclampsia, premature birth, low birth weight, and fetal growth restriction. This study aims to determine the existing literature on the impact of COVID-19 on anxiety in pregnant women. This study used a systematic literature review method. The population in this study were journals from the Pubmed, Science Direct, Sage, Emerald, and Proquest databases published between 2020 and 2021. Result of study was a total of 15 of the 675 articles met the inclusion criteria. This study found that 8 out of 15 articles experienced an increase in the prevalence of anxiety in pregnant women by more than half a percent (90.5%; 57.8%; 77%; 64.5%) and experienced an increase in anxiety prevalence by more than a quarter percent ( 43.9%; 46.3%; 25.6%; 37.5%. In addition, this study found differences in the anxiety of pregnant women between before COVID-19 and during COVID-19 Pandemics. Anxiety in pregnant women included gestational age, demographics, socioeconomic status, knowledge, social support, and physical activity. The COVID-19 pandemic could increase anxiety in pregnant women. Mental health of pregnant women should be one of the priorities in public health to improve the welfare of pregnant women. Policymakers and health planners need to consider mental health in pregnant women in designing procedures to deal with the COVID-19 pandemic.